Design and construction of a numerical over current relay - Rumi, Md Rayhanul Amin; Hossain, S.M. Amanat; Hanif, Razaul Haider; Mostafa, Mahdi Md (BRAC University, 2016)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2015.